2020 31st Annual SEMI Advanced Semiconductor Manufacturing Conference (ASMC) 2020
DOI: 10.1109/asmc49169.2020.9185349
|View full text |Cite
|
Sign up to set email alerts
|

Spectroscopic Ellipsometry Imaging for Process Deviation Detection via Machine Learning Approach

Abstract: Spectroscopic ellipsometry is a very sensitive metrology technique to accurately measure the thickness and the refractive index of the different layers present on specific dedicated metrology targets. In parallel, optical defectivity techniques are widely implemented in production lines to inspect a large number of dies and catch physical and patterning defects during the process flow. It becomes then of interest to explore a new approach overlapping metrology and defectivity by using the sensitivity of metrol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…Blanket nitride layers on silicon were first characterized by modelling with an industrial in-line ellipsometry system as already demonstrated in [6]. In this study, a strong inhomogeneity with a diametrical signature was detected in the refractive index of the layer, even though the layers thickness was relatively constant (> 0.05% variation) on the wafer surface (Fig.…”
Section: ) Blanket Wafer Analysismentioning
confidence: 58%
“…Blanket nitride layers on silicon were first characterized by modelling with an industrial in-line ellipsometry system as already demonstrated in [6]. In this study, a strong inhomogeneity with a diametrical signature was detected in the refractive index of the layer, even though the layers thickness was relatively constant (> 0.05% variation) on the wafer surface (Fig.…”
Section: ) Blanket Wafer Analysismentioning
confidence: 58%